Prevalence of Porphyromonas gingivalis fimA II genotype in generalized aggressive periodontitis patients - Rodrigues, Richelle Soares (2017)
Purpose: The objective of this study was to evaluate the prevalence of Porphyromonas gingivalis (Pg) and its filmA II genotype in a sample of Brazilian patients with generalized aggressive periodontitis (GAgP) and to correlate the presence of each pathogen/genotype eith clinical parameters. Methods: We used polymerase chain reaction (PCR) to evaluate the presence of Pg and filmA II genotype in subgingival plaque samples collected from the deepest site of 45 Brazilian patients aged 15-40 years with GAgP and correlated findings with age and clinical parameters (plaque index, gingival bleeding index, probing depth and clinical attachment loss). Results: Pg was identified in 64.4% patients. FilmA II genotype was present in 82.6% of Pg-positive patients. The presence of Pg and filmA II genotype was significantly associated with greater clinical attachment loss at the sampled periodontal site. Pg-positive patients were slightly older than Pg-negative patients. Conclusions: Pg and filmA II genotype were highly prevalente in Brazilian patients with GAgP. Pg was more commonly observed in slightly older individuals and in sites with more clinical attachment loss.